2009
DOI: 10.1093/ntr/ntp080
|View full text |Cite
|
Sign up to set email alerts
|

Estimating smokers' mouth-level exposure to select mainstream smoke constituents from discarded cigarette filter butts

Abstract: We believe that this method provides excellent versatility and throughput for the estimation of mouth-level exposure to a wide range of toxins in cigarette smoke under naturalistic conditions. In addition, this method allows a far more accurate measure of exposure both from a single cigarette as well as from daily smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 13 publications
0
42
1
Order By: Relevance
“…The study endpoints included a broad array of biomarkers measured in blood, plasma, 24-h urine, exhaled breath, smoked filters/MLE (Morin et al, 2011;Nelson et al, 2011;Polzin et al, 2009;Shepperd et al, 2011;St. Charles et al, 2009) and two subjective questionnaires to monitor smoking urges or withdrawal symptoms (Cox et al, 2001;Hughes and Hatsukami, 1986;Tiffany and Drobes, 1991).…”
Section: Experimental Designmentioning
confidence: 99%
“…The study endpoints included a broad array of biomarkers measured in blood, plasma, 24-h urine, exhaled breath, smoked filters/MLE (Morin et al, 2011;Nelson et al, 2011;Polzin et al, 2009;Shepperd et al, 2011;St. Charles et al, 2009) and two subjective questionnaires to monitor smoking urges or withdrawal symptoms (Cox et al, 2001;Hughes and Hatsukami, 1986;Tiffany and Drobes, 1991).…”
Section: Experimental Designmentioning
confidence: 99%
“…Solanesol, a nonvolatile, stable, and tobacco-specific compound, can serve as a proxy for other chemicals in smoke. Published results indicate excellent linear correlation between cigarette filter solanesol levels and mainstream smoke nicotine or TSNAs levels (9). However, our experiments indicated that the solanesol to BaP relation was not a perfect linear fit.…”
Section: Introductionmentioning
confidence: 52%
“…In filter analysis, we found that direct measurement of BaP in cigarette filters provides a better linear relation with mainstream smoke levels than solanesol, although solanesol does serve as an excellent predictor for measuring chemicals in cigarette smoke including (9). Unlike solanesol and the majority of nicotine and TSNAs trapped in cigarette filters which are transferred from tobacco to smoke, BaP in smoke is a product of various combustion processes.…”
Section: Discussionmentioning
confidence: 95%
“…As the objective of the study was to investigate smokers in their own environment, nicotine equivalents and NNAL were chosen as the biomarkers of exposure as they are tobacco-specific and therefore not influenced by environmental and dietary sources (Hatsukami et al, 2006;Hecht, 2002). In addition, the use of the part-filter methodology has gained popularity recently and represents a non-invasive technique to provide estimates of MLE to nicotine and tar, in the subject's own environment (Clayton et al, 2010;Ding et al, 2012;Pauly et al, 2009;Polzin et al, 2009). Mendes et al (2008) aimed to address these concerns by inclusion of both a randomized, controlled, short-term phase and an unrestricted long-term follow-up phase in assessing the effects of forced switching.…”
Section: Discussionmentioning
confidence: 99%